BEBERAPA PERSPEKTIF TEORI PENYUSUNAN BAHAN AJAR KETERAMPILAN BERBAHASA INDONESIA - Pratiwi, Yuni (Diksi, 2015)
Facing continuous global changes, the Indonesian government views that a centralized curriculum is incapable of accommodating the development of knowledge and community needs in the local, national, and global levels. A competence-based curriculum is constructed with an expectation that in the national education system graduates have competitive and comparative advantages. The Indonesian Language subject equips students with awareness that the language is the national identity that unifies Indonesian people as a nation and simultaneously the subject develops their linguistic and communicative competence. Teachers’ understanding of the scope of the competence contents and theoretical perspectives in instructional materials development affects the level of the competence attainment. Theoretical perspectives help teachers to develop instructional materials for language skills relevant to students’ communicative needs in real life. Keywords: perspective, instructional materials for the Indonesian language skills, School-Based Curriculum